EFL Vocational High School Students’ Challenges in Writing Thesis Statements: Problems and Contributing Factors - Putri Alya Fadiyah; Eva Rahmawati; Natasya Pradini Putri (English Department, Universitas Negeri Surabaya, 2025)
Thesis statement is important in producing analytical exposition texts. However, many EFL vocational high school students encounter several problems in developing a thesis statement. This study aims to identify the problems experienced by tenth-grade students while writing thesis statements and to investigate the underlying factors causing to these problems. A qualitative case study approach was used in this study, involving students majoring in Electrical Engineering at a public vocational high school in Surabaya, Indonesia. Data were collected through document analysis from thirty students’ thesis statement and semi-structured interviews with six students. The findings revealed several common problems, particularly in formulating arguable claims, identifying clear subjects and contexts, and applying correct grammar and mechanics. Frequent errors included the use of non-debatable claims and incorrect capitalization. Contributing factors included students’ limited vocabulary and grammar knowledge, low motivation, negative attitudes toward English, lack of practice, time constraints, and lack of feedback from teachers. These results suggest the need for more focused instruction and practice in writing thesis statements.